Pancreaticoduodenectomy for severe duodenal stenosis and biliary-duodenal fistula induced by groove pancreatitis due to repetitive duodenal ulcers: A pediatric case report - Yuta Nishikawa; Yukihiro Okuda; Akira Kurita; Keinosuke Hizuka; Shin-ichiro Hagiwara; Hiroaki Terajima (Elsevier, 2023)
Groove pancreatitis (GP), an uncommon form of recurrent or chronic focal pancreatitis, is exceedingly rare in children. This report describes a case of pancreaticoduodenectomy performed for severe duodenal stenosis and biliary-duodenal fistula induced by GP in a child. A 14-year-old boy presented to a gastroenterologist due to repeated abdominal pain for 5 years. Esophagogastroduodenoscopy, computed tomography, and magnetic resonance cholangiopancreatography suggested a duodenal ulcer that was possibly associated with GP. The patient was referred to our hospital for further examination. Endoscopic retrograde cholangiopancreatography revealed stenosis of the main pancreatic duct and ectopic opening of the common bile duct into the duodenum (biliary-duodenal fistula). An internal pancreatic stent was placed via the papilla of Vater to treat obstructive pancreatitis, while an internal biliary stent was placed through the fistula to prevent cholangitis. Replacement of the pancreatic stent was deemed impossible due to exacerbation of the duodenal stenosis. Considering the limitations of repeated endoscopic treatment, radical surgical intervention and subtotal stomach-preserving pancreaticoduodenectomy were performed. Relapse of previous abdominal symptoms and surgery-associated long-term complications did not occur postoperatively. In pediatric GP cases without any contributing factors of chronic pancreatitis, such as pancreas divisum, GP is often attributable to repetitive duodenal ulcers.